CLINICAL, FAEMATOLOGICAL AND BIOCHEI‘./ECAL STUDIES ON ANAPLASMOSIS IN LOCAL BUFETALOES IN MOSUL, AREA - Alsaad, K.M (The Iraqi Journal of Veterinary Medicine, 2022)
Fourty ﬁve local buffaloes naturally infected with A. marginal age of 2-5 years. Clinical signs, present parasireamia haematological and biochemical changes were studied. Thin thick blood smears Stained with Gimsas stain were used to identify the parasite. The results indicated that most of the infected were suffering from mild form of infection and the 1I11p01”l11I1E’ clinical signs observed were mild rise of body temperature, increase respiratory and plus rate, weal: ruminal contraction and generalized weakness. Palcness and iteration of mucous membrane, loss appetite, nasal and ocular discharge, coughing, salivation, atarcp, constipation, diarrhea, and rccumbancy. Statistical analysis showc increase (P<0.01) in body temperature, respiratory and pulsera wlﬂc nigrriﬁcant decrease (P<0.01) in ruminal contraction We. observed. Parasiteamia in infected animals ranged from 1.3- 5.2%. Values of red blood cell, haemoglobin and packed cell volume were signiﬁcantly low (P<0.01). Total leulcocyric and neutrophils count was signiﬁcantly increase (P<0.0l). and (P<0.05) respectively. Blood indices values showed a signiﬁcant increase in (MCHC) (P<0.0l) while (MCV) values showed no difference, reticulocytes were also present mildly biochemical changes indicated higher levels of AST. Total bilirubin (P<0.01). Total protein concentration was less (P<0.01) and no difference was observed inALT and blood urea nitrogen levels between infected and control animals.